Social Emotional Character of Bullying Perpetrators in Elementary School with Varying Levels of Aggression - Asrie Refi Salshabila, Dzawin; Muhaimin, Muh; Rofiqoh, Naili (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
Elementary school bullying is still a widespread and problematic phenomenon that negatively affects both the bully and the victim. The purpose of this study is to explore the social and emotional character of bullying perpetrators within an elementary school context as a mechanism for identifying intervention strategies that are both responsive and specific. This research utilized a descriptive qualitative method with a case study involving six male students in grade 5 from Public Elementary School 1 Sowan Lor who are classified as bullying perpetrators. Data were gathered through the use of in-depth interviews, classroom observations, and pertinent documentation, and analyzed following Miles and Huberman’s interactive model. Findings of this study suggest that two students engaged in high-intensity bullying characterized by emotionally dysregulated, frequently aggressive verbal and physical acts of bullying targeted towards peers who were interpreted to be attention-seeking. The other four students demonstrated moderate levels of bullying– their behaviour influenced by peer relations and provocation, but with a greater degree of emotional control most of the time. These findings underscore the salience of emotional instability, low empathy, and peer influence for bullying behavior. This emphasizes the need to introduce early character-based educational incentives that build learners’ emotional intelligence, empathy, and positive social connectedness, ensuring all young pupils experience a school climate where they feel safe and supported.